Influence of Therapeutic Communication on the Recovery Level of COVID-19 Patients - Dicky Endrian Kurniawan; Kholifatur Rosyidah; Swastika Ayu Olyvera; Shafira Anindyah; Enggal Hadi Kurniyawan; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Bagus Dwi Cahyono; Evy Aristawati; Nurul Huda (Health and Technology Journal (HTechJ), 2024)
The COVID-19 pandemic, which has occurred since 2020 in Indonesia, has had many impacts on society in various aspects, one of the main ones being mental and social conditions that cause stress. One thing that has an influence is the health service environment. In nursing, communication is vital in helping and building interactions between nurses and patients, and it is called therapeutic communication. This literature review aims to help analyze nurses' therapeutic communication regarding the recovery of COVID-19 patients. The method used is a search in reviews literature using three databases, Google Scholar, PubMed, and Science Direct, with the publication year 2019-2023, with the initial step of identifying keywords and then screening and filtering to get ten suitable articles from a total of 3,846 articles found. The results of 10 journals that have gone through these stages or methods state that there is no significant process in each stage of communication on patient satisfaction. In addition, there was no significant relationship between nurses' skills and how nursing care was implemented. However, therapeutic communication is proven to reduce anxiety in patients and families. The nurse's good therapeutic communication experience is evidenced by the support system, effective coping, and hope for the patient's recovery. One of the latest models in its implementation is the TAGEET model, which encourages psychological support for patients. Female gender and nurses have a relationship with therapeutic communication. If communication is lacking, it will impact the psychology of patients and nurses and the patient's recovery rate. As a nurse, you should be able to interpret the techniques and stages of good therapeutic communication to increase a patient's recovery level.